Assessing Multicultural Competence of Helping-Profession Students. (2nd January 2016) - Hladik, Jakub
Abstract: In this article, I focus on assessing multicultural competence of helping-profession students. The Multicultural Competence Scale of Helping-Profession Students was used for data collection. The aim of the research was to find out the level of students' multicultural competence due to the current lack of this information in Central Europe. Generally, students assess their multicultural competence on the higher level. There is a significant relationship between the students' study degree and the level of their multicultural competence. Multicultural activity was shown as an important predictor of multicultural knowledge. Also, multicultural knowledge was identified as a significant predictor of multicultural communication skills.